Catalyst component for olefin polymerization, preparation method of catalyst component, catalyst for olefin polymerization and application of catalyst component

By using a catalyst component preparation method without using an organic aluminum compound, the magnesium halide alcohol support is treated with a titanium-containing compound, and combined with an agglomerating agent and a reinforcement agent, the problems of safety and high energy consumption of catalyst preparation in the prior art are solved, and the effect of good catalyst particle morphology and low polymer fine powder content is achieved.

CN119708300AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311271050.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The prior art uses organoaluminum compounds and high energy-consuming support heating equipment when preparing catalysts, which poses safety hazards and high energy consumption problems. The catalyst is prone to shattering during polymerization, resulting in a high polymer fine powder content.

Method used

The catalyst component preparation method without using organoaluminum compounds was used to treat the spherical magnesium halide alcohol support by titanium-containing compounds, and combined with agglomerating agent and reinforcement, a catalyst with good particle morphology was prepared, which avoided the prepolymerization process and simplified the preparation process.

Benefits of technology

The catalyst is prepared safely and low-energy-consuming. The catalyst particles are spherical in shape and are not easy to break during polymerization. The resulting polymer fine powder content is very small, which is suitable for gas phase and slurry polymerization processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004479650950000141
    Figure BDA0004479650950000141
Patent Text Reader

Abstract

The invention discloses a catalyst component for olefin polymerization, a preparation method of the catalyst component, a catalyst for olefin polymerization and application of the catalyst component. The catalyst component for olefin polymerization is prepared from raw materials including an intermediate, an agglomeration agent and a reinforcing agent, the intermediate is prepared from raw materials including a magnesium halide alcohol adduct and a titanium-containing compound. The catalyst component provided by the invention is simple and safe in preparation process, and the catalyst particles are spherical and are not easy to break when catalyzing olefin polymerization; the obtained polymer particles are spherical, the fine powder content is extremely low, and the method is suitable for a gas phase polymerization process and an olefin slurry polymerization process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst components for olefin polymerization, and more particularly to catalyst components for olefin polymerization and a preparation method thereof, and catalysts for olefin polymerization and applications thereof. Background Art

[0002] Whether it is the slurry polymerization process or the gas phase polymerization process of olefins, the catalyst is required to have good particle morphology, not easy to break during the polymerization process, and low content of polymer fine powder. This is particularly important in the gas phase polymerization process of olefins.

[0003] European patent document EP1572756A discloses a catalyst prepared using a spherical magnesium chloride carrier. The catalyst prepared by this method has a good particle morphology, and the polymer production device includes a prepolymerization process to reduce the breakage of the catalyst during the polymerization reaction and reduce the fine powder content of the polymer. The preparation process of the catalyst includes: firstly reducing the ethanol content by heating the carrier, and then treating the carrier with an organic aluminum compound and titanium tetrachloride. The catalyst prepared by this method has a high polymerization activity, but the preparation process uses dangerous organic aluminum compounds, and the carrier heating equipment consumes a lot of energy.

[0004] In order to omit the prepolymerization process in the polymer production device, European patent document EP2285840A discloses another catalyst prepared using a spherical magnesium chloride carrier. The preparation process of the catalyst includes: firstly reducing the ethanol content by heating the carrier, then treating the carrier with titanium tetrachloride to obtain the catalyst, and then prepolymerizing with an organic aluminum compound. The catalyst prepared by this method has a high polymerization activity, but dangerous organic aluminum compounds are used in the prepolymerization, and the carrier heating equipment consumes a lot of energy.

[0005] Chinese patent documents CN102020732A and CN102050897A both disclose catalysts prepared using spherical magnesium chloride carriers, and the prepared catalysts have high polymerization activity. Chinese patent document CN102020732A first treats the carrier with an organic aluminum compound, and then treats the carrier with titanium tetrachloride to obtain a catalyst; this preparation process uses dangerous organic aluminum compounds, and its safety needs to be further improved. Chinese patent document CN102050897A first heats the carrier to reduce the ethanol content, and then treats the carrier with titanium tetrachloride to obtain a catalyst; this preparation process uses a very energy-consuming carrier heating device, and the equipment investment is large.

[0006] Therefore, how to provide a catalyst with a simple and safe preparation process, good catalyst particle morphology, not easy to break when catalyzing olefin polymerization, and extremely low content of fine polymer powder is an important research direction in this field. Summary of the invention

[0007] In order to solve the problems in the prior art, the present invention provides a catalyst component for olefin polymerization and a preparation method thereof, a catalyst for olefin polymerization and an application thereof. The catalyst component preparation process of the present invention is simple and safe, the catalyst particles are spherical, and are not easily broken when catalyzing olefin polymerization; the obtained polymer particles are spherical, and the fine powder content is extremely small, and the catalyst is suitable for gas phase polymerization process and olefin slurry polymerization process.

[0008] One of the objects of the present invention is to provide a catalyst component for olefin polymerization, wherein the catalyst component for olefin polymerization is prepared from raw materials including an intermediate, a coagulating agent and a reinforcing agent;

[0009] The intermediate is prepared from raw materials including magnesium halide alcoholate and titanium-containing compound.

[0010] In the catalyst component for olefin polymerization described in the present invention, preferably,

[0011] The magnesium halide alcoholate is a reaction product of a magnesium halide and a low-carbon alcohol;

[0012] Preferably,

[0013] The content of the low-carbon alcohol in the magnesium halide alcoholate is 10wt% to 60wt%; for example, 10, 12, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60wt% and any range between any two of the above values; or,

[0014] The molar ratio of the lower alcohol to the magnesium halide is 0.25 to 3, preferably 2 to 3, and more preferably 2 to 2.8.

[0015] In the catalyst component for olefin polymerization described in the present invention, preferably,

[0016] The magnesium halide alcoholate is selected from at least one of magnesium chloride alcoholates;

[0017] Preferably, the low-carbon alcohol is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol or isobutanol; most preferably, it is ethanol.

[0018] The preparation method of magnesium halide alcoholate described in the present invention is with reference to Chinese patent CN1091748A (taking magnesium chloride alcoholate as example), and the steps are as follows: anhydrous magnesium halide such as magnesium dichloride and alcohol are reacted by a certain ratio to generate magnesium chloride alcoholate melt, after high-speed stirring and dispersion in a dispersant, rapidly cooled to form microspherical solid particles of magnesium chloride alcoholate, and then obtained after washing and drying. Dispersant adopts hydrocarbon solvents such as kerosene, paraffin oil, vaseline oil, white oil etc., and also adds some surfactants or organosilicon compounds. Alcohol includes methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol and other high-carbon fatty alcohol compounds, wherein preferred ethanol.

[0019] In the catalyst component for olefin polymerization described in the present invention, preferably,

[0020] The titanium-containing compound is selected from the general formula (I) Ti(OR) m Cl 4-m At least one of the compounds shown; wherein R is C2~C 20 Hydrocarbyl, 0≤m≤4;

[0021] Preferably, R is C2~C 10 A saturated or unsaturated straight chain, branched chain or cyclic chain hydrocarbon group;

[0022] More preferably, R is a C2-C6 saturated or unsaturated straight chain, branched chain or cyclic chain hydrocarbon group;

[0023] Still more preferably, the titanium-containing compound is selected from at least one of titanium tetrachloride, tetraethyl titanate or tetrabutyl titanate, and most preferably is titanium tetrachloride.

[0024] In the catalyst component for olefin polymerization described in the present invention, preferably,

[0025] The agglomerating agent is selected from at least one of C1-C8 alkyl ester compounds;

[0026] Preferably, the agglomerating agent is selected from at least one of C1 to C6 alkyl ester compounds;

[0027] Further preferably, the agglomerating agent is selected from at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate or isopropyl acetate, and most preferably is ethyl acetate.

[0028] In the catalyst component for olefin polymerization described in the present invention, preferably,

[0029] The reinforcing agent is selected from at least one of styrene-butadiene block copolymers;

[0030] Preferably,

[0031] In the styrene-butadiene block copolymer, the mass content of butadiene is 3 to 97%, preferably 10 to 90%; and / or,

[0032] The block type in the styrene-butadiene block copolymer is linear or branched;

[0033] More preferably,

[0034] The styrene-butadiene block copolymer is selected from at least one of styrene-butadiene diblock copolymer and its derivatives, styrene-butadiene-styrene triblock copolymer and its derivatives;

[0035] Still further preferably, the styrene-butadiene diblock copolymer derivative is selected from at least one of hydrogenated styrene-butadiene copolymer, maleic anhydride grafted styrene-butadiene copolymer or acrylic acid grafted styrene-butadiene copolymer;

[0036] The styrene-butadiene-styrene triblock copolymer derivative is at least one selected from hydrogenated styrene-butadiene-styrene copolymer, maleic anhydride grafted styrene-butadiene-styrene copolymer or acrylic acid grafted styrene-butadiene-styrene copolymer.

[0037] In the catalyst component for olefin polymerization described in the present invention, preferably,

[0038] The molar ratio of the titanium-containing compound to the magnesium halide alcoholate is 1 to 100; preferably 5 to 50; for example, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 and any range between any two of the above values; and / or,

[0039] The weight ratio of the intermediate to the agglomerating agent is 0.5 to 50, preferably 1 to 25; for example, 0.5, 1, 2, 4, 6, 8, 10, 10, 15, 20, 25, 30, 35, 40, 45, 50 and any range between any two of the above values; and / or,

[0040] The weight ratio of the intermediate to the enhancer is 10 to 1000, preferably 20 to 500; for example, 10, 20, 50, 100, 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000 and any range between any two of the above values.

[0041] The second object of the present invention is to provide a method for preparing a catalyst component for olefin polymerization, comprising the following steps:

[0042] (1) reacting a magnesium halide alcoholate with a titanium-containing compound in a solvent, separating the solid from the liquid, and then reacting the separated solid with the titanium-containing compound in a solvent for a second time, washing, and drying to obtain an intermediate;

[0043] (2) reacting the enhancer, the intermediate and the agglomerating agent in a solvent under a protective atmosphere to obtain the catalyst component;

[0044] It is preferably used for the preparation of the catalyst component for olefin polymerization as one of the objects of the present invention.

[0045] In the method for preparing the catalyst component for olefin polymerization of the present invention, preferably,

[0046] In step (1), the molar ratio of the titanium-containing compound to the magnesium halide alcoholate is 1 to 100, preferably 5 to 50; and / or the molar ratio of the titanium-containing compound for the primary reaction to the titanium-containing compound for the secondary reaction is 0.1 to 10, preferably 0.5 to 5;

[0047] Preferably,

[0048] The solvents used in the primary reaction and the secondary reaction are independently selected from C4 to C 20 Alkane or aromatic solvent; preferably, the solvents used in the primary reaction and the secondary reaction are each independently selected from at least one of pentane, hexane, heptane, toluene, isobutane and cyclohexane; and / or,

[0049] In a single reaction, the concentration of the magnesium halide alcoholate in the reaction system is 1wt% to 15wt%, preferably 2wt% to 10wt%; for example, 1, 2, 5, 10, 15wt% and any range between any two of the above values; and / or,

[0050] The temperature of the primary reaction and the secondary reaction are independently selected from (-80)°C to 150°C, preferably (-50°C) to 120°C; for example, -80, -50, -30, 0, 30, 60, 90, 120, 150°C and any range between any two of the above values; and / or,

[0051] The time of the primary reaction and the secondary reaction are independently selected from 2 h to 20 h, preferably 4 h to 10 h; for example, 2, 4, 5, 10, 15, 20 h and any range between any two of the above values; and / or,

[0052] The drying is carried out by blowing with protective gas.

[0053] In the method for preparing the catalyst component for olefin polymerization of the present invention, preferably,

[0054] In step (2),

[0055] The weight ratio of the intermediate to the agglomerating agent is 0.5 to 50, preferably 1 to 25; for example, 0.5, 1, 2, 4, 6, 8, 10, 10, 15, 20, 25, 30, 35, 40, 45, 50 and any range between any two of the above values; and / or,

[0056] The weight ratio of the intermediate to the enhancer is 10 to 1000, preferably 20 to 500; for example, 10, 20, 50, 100, 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000 and any range between any two of the above values; and / or,

[0057] The concentration of the intermediate in the reaction system is 1wt% to 15wt%, preferably 2wt% to 10wt%; for example, 1, 2, 5, 10, 15wt% and any range between any two of the above values; and / or, the reaction temperature is 0°C to 90°C, preferably 10°C to 50°C; for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90°C and any range between any two of the above values; and / or,

[0058] The reaction time is 0.5h to 6h, preferably 1h to 3h; for example, 0.5, 1, 2, 3, 4, 5, 6h and any range between any two of the above values;

[0059] Preferably,

[0060] In step (2), the dispersion of the enhancer is mixed with the dispersion of the intermediate and the agglomerating agent, and then reacted, and then washed and dried to obtain the catalyst component;

[0061] More preferably,

[0062] The solvents used in the dispersion of the enhancer and the dispersion of the intermediate are independently selected from C4 to C 20 An alkane solvent or an aromatic solvent; preferably at least one independently selected from pentane, hexane, heptane, toluene, isobutane, and cyclohexane; and / or,

[0063] The drying is carried out by blowing with protective gas.

[0064] The third object of the present invention is to provide a catalyst for olefin polymerization:

[0065] The invention comprises at least one of (a) the catalyst component for olefin polymerization described in any one of the first objects of the present invention and the catalyst component for olefin polymerization prepared by any one of the methods described in any one of the second objects of the present invention;

[0066] (b) at least one organoaluminum compound of the general formula AlR'3, wherein the three R's are independently selected from an alkyl group or a halogen-substituted alkyl group.

[0067] In the catalyst for olefin polymerization described in the present invention, preferably,

[0068] The three R's in the organoaluminum compound are independently selected from C1-C8 alkyl groups or C1-C8 alkyl groups substituted with chlorine; preferably, at least one of the three R's in the organoaluminum compound is a C1-C8 alkyl group;

[0069] Further preferably, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum monochloride and ethylaluminum dichloride; and / or,

[0070] In the catalyst for olefin polymerization, the molar ratio of aluminum to titanium is 1-1000, preferably 10-100.

[0071] The fourth object of the present invention is to provide a catalyst component for olefin polymerization as described in any one of the present invention, the second object of the present invention is to provide a catalyst component for olefin polymerization prepared by the method described in any one of the present invention, and the third object of the present invention is to provide a catalyst for olefin polymerization reaction as described in any one of the present invention in olefin polymerization reaction; preferably, the olefin is selected from one or more of ethylene, propylene, butene, hexene or octene.

[0072] The catalyst of the present invention may be used together with another co-catalyst or electron donor, and may also be used in combination with one or more Ziegler-Natta catalysts or non-Ziegler-Natta catalysts.

[0073] The catalyst described herein can be used in different polymerization processes, including gas phase polymerization process and slurry polymerization process. The catalyst system described herein can be used in the polymerization or copolymerization reaction of olefins.

[0074] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0075] Compared with the prior art, the present invention has at least the following advantages:

[0076] The prior art uses an organic aluminum compound to treat a carrier during the catalyst preparation stage and then loads titanium tetrachloride and other titanium-containing compounds. The present invention does not use an organic aluminum compound during the catalyst component preparation stage and is therefore safer.

[0077] The catalyst component and the corresponding catalyst in the present invention do not require a catalyst prepolymerization process and can be directly applied to olefin polymerization; the catalyst component uses a titanium-containing compound (such as titanium tetrachloride) to treat a spherical magnesium halide alcoholate carrier twice, and the preparation process does not contain a heating dealcoholization step, so the preparation process is simpler and the cost is lower.

[0078] The invention finds that a spherical magnesium halide alcohol compound carrier is treated twice with a titanium-containing compound (such as titanium tetrachloride) to prepare an intermediate, and then treated with a coagulating agent and a reinforcing agent; it is found that the use of a coagulating agent can reduce catalyst fine powder, thereby reducing the content of polymer fine powder; the use of a reinforcing agent can reduce the fragmentation of the catalyst in the polymerization reaction, and further reduce the content of fine powder in the polymer; the coagulating agent and the reinforcing agent can be added at the same time for reaction; or the coagulating agent can be added first for reaction, and then the reinforcing agent can be added for reaction, and the effect is the same.

[0079] The catalyst component preparation process of the invention is simple and safe, the catalyst particles are spherical and are not easily broken when catalyzing olefin polymerization; the obtained polymer particles are spherical and have very little fine powder content, and are suitable for gas phase polymerization processes and olefin slurry polymerization processes. DETAILED DESCRIPTION

[0080] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0081] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0082] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0083] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0084] Test method:

[0085] 1. Particle size distribution of carrier and catalyst: MASTERSIZE particle size distribution analyzer, n-hexane as dispersant, measuring range 0.01~3500μm.

[0086] 2. The content of metal (titanium) in the catalyst system: Inductively coupled plasma emission spectroscopy (ICP).

[0087] 3. Determination method of bulk density: DIN-53194

[0088] The synthetic method of the magnesium chloride alcoholate adopted in the present invention is as follows:

[0089] In a 250 ml glass reactor equipped with a reflux condenser, a mechanical stirrer and a thermometer, which was replaced by nitrogen, 37.8 ml of anhydrous ethanol and 21.3 g of anhydrous magnesium chloride were added, and the temperature was raised under stirring. After the magnesium chloride was completely dissolved, 75 ml of white oil and 75 ml of silicone oil were added, and the temperature was maintained at 120° C. for a certain period of time. In another reaction bottle with a high-speed stirrer of 500 ml volume, 112.5 ml of white oil and the same volume of silicone oil were added in advance, and the mixture was preheated to 120° C. The mixture prepared above was quickly pressed into the second reactor, and the temperature was maintained at 120° C., and the mixture was stirred at a high speed of 4000 rpm for three minutes. Under stirring, the material was transferred to a third reactor in which 1600 ml of hexane was added in advance and cooled to -25° C., until the material transfer was completed, and the final temperature did not exceed 0° C. The silicone oil and white oil were washed off with hexane and vacuum dried to obtain 45.7 g of spherical magnesium chloride alcoholate. The composition of magnesium chloride alcoholate was MgCl22.56C2H5OH, the average particle size was 50.1 microns, and the alcohol content was 56.0 wt%.

[0090] Example 1

[0091] Preparation of catalyst components

[0092] (1) Preparation of intermediates

[0093] Under nitrogen protection, add 5.0 g of magnesium chloride alcoholate and 50 ml of n-hexane to a 500 ml glass reactor, cool to -30 °C; slowly add 50 ml of titanium tetrachloride and stir for 2 hours; slowly heat to 70 °C and stir for 2 hours. Cool to 50 °C, let stand and filter the mother liquor; add 50 ml of n-hexane and then add 50 ml of titanium tetrachloride again to react, the reaction steps are the same as above. After the reaction is completed, wash three times with 50 ml of n-hexane, and dry with nitrogen to obtain 3.8 g of an intermediate with good fluidity.

[0094] (2) Preparation of Catalyst

[0095] Under nitrogen protection, the intermediate obtained in step (1) and 50 ml of n-hexane were added to a 500 ml glass reactor, 0.5 ml of ethyl acetate was added, and 1 ml of a hexane solution (10 g / L) of a styrene-butadiene-styrene triblock copolymer (Kraton FG1901X, wherein the butadiene content is 70%) was added, and the temperature was raised to 50° C. and stirred for 2 hours. After the reaction was completed, the mixture was washed three times with 50 ml of n-hexane and dried with nitrogen to obtain a catalyst with good fluidity and an average particle size of 36.7 μm.

[0096] Elemental analysis (ICP): Ti: 3.96% (wt).

[0097] Ethylene polymerization

[0098] 1L hexane, 1mmol triethylaluminum and a certain amount (10mg) of catalyst components were added to a 2L stainless steel stirred tank, and the temperature was raised to 85°C; 0.28MPa of hydrogen was added, and ethylene was added to maintain the total pressure of the system at 1.03Mpa, and the polymerization reaction was carried out for 2 hours. After the reaction was completed, the polyethylene powder was dried and collected and weighed, and the polymerization activity was calculated. The catalyst prepared above was used for polymerization reaction, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0099] Example 2

[0100] Preparation of catalyst components

[0101] Except that the amount of ethyl acetate was changed from 0.5 ml to 1 ml, other conditions were the same as in Example 1, and the average particle size was 37.5 μm.

[0102] Elemental analysis (ICP): Ti: 3.89% (wt).

[0103] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0104] Example 3

[0105] Preparation of catalyst components

[0106] Except that the amount of ethyl acetate was changed from 0.5 ml to 1.5 ml, other conditions were the same as in Example 1, and the average particle size was 38.4 μm.

[0107] Elemental analysis (ICP): Ti: 3.77% (wt).

[0108] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0109] Example 4

[0110] Preparation of catalyst components

[0111] Except that the amount of ethyl acetate was changed from 0.5 ml to 2 ml, other conditions were the same as in Example 1, and the average particle size was 39.2 μm.

[0112] Elemental analysis (ICP): Ti: 3.62% (wt).

[0113] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0114] Example 5

[0115] Preparation of catalyst components

[0116] Except that the amount of ethyl acetate was changed from 0.5 ml to 2.5 ml, other conditions were the same as in Example 1, and the average particle size was 40.3 μm.

[0117] Elemental analysis (ICP): Ti: 3.51 wt%.

[0118] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0119] Example 6

[0120] Preparation of catalyst components

[0121] Except that the amount of the hexane solution of the styrene-butadiene-styrene triblock copolymer was changed to 2 ml, other conditions were the same as those in Example 1, and the average particle size was 36.8 μm.

[0122] Elemental analysis (ICP): Ti: 4.00% (wt).

[0123] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0124] Example 7

[0125] Preparation of catalyst components

[0126] Except that the amount of the hexane solution of styrene-butadiene-styrene triblock copolymer was changed to 5 ml, other conditions were the same as those in Example 1, and the average particle size was 37.2 μm.

[0127] Elemental analysis (ICP): Ti: 4.05% (wt).

[0128] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0129] Comparative Example 1

[0130] Preparation of catalyst components

[0131] Except that ethyl acetate and the hexane solution of styrene-butadiene-styrene triblock copolymer were not added, other conditions were the same as those in Example 1, and the average particle size was 35.8 μm.

[0132] Elemental analysis (ICP): Ti: 4.17% (wt).

[0133] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0134] Comparative Example 2

[0135] Preparation of catalyst components

[0136] Except that ethyl acetate was not added, other conditions were the same as in Example 1, and the average particle size was 36.0 μm.

[0137] Elemental analysis (ICP): Ti: 4.05% (wt).

[0138] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0139] Comparative Example 3

[0140] Preparation of catalyst components

[0141] Except that the hexane solution of styrene-butadiene-styrene triblock copolymer was not added, other conditions were the same as those in Example 1, and the average particle size was 36.6 μm.

[0142] Elemental analysis (ICP): Ti: 3.98% (wt).

[0143] The conditions for the ethylene slurry polymerization of the catalyst were the same as those in Example 1. The catalyst prepared above was used for polymerization, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1. The polymer screening results are shown in Table 2.

[0144] The above-prepared catalyst was used for polymerization reaction, and the corresponding polymerization activity and polymer bulk density results are shown in Table 1.

[0145] Table 1 Polymerization activity of catalysts and polymer bulk density

[0146] Polymerization activity kgPE / gCat. Bulk density of polymer Example 1 13.9 0.35 Example 2 13.8 0.34 Example 3 13.5 0.34 Example 4 13.2 0.33 Example 5 13.0 0.33 Example 6 13.6 0.34 Example 7 11.9 0.32 Comparative Example 1 14.2 0.36 Comparative Example 2 14.0 0.35 Comparative Example 3 14.2 0.36

[0147] Table 2 Particle size distribution of polymers (weight percentage)

[0148]

[0149] From the above results, it can be seen that adding only the hexane solution of styrene-butadiene-styrene triblock copolymer as a reinforcing agent during the preparation of the catalyst can reduce the content of polymer fine powder, but cannot eliminate polymer fine powder less than 150um. If ethyl acetate is added as a coagulant at the same time, not only the size of the catalyst particles can be enlarged, but also the size of the polymer particles can be increased, and polymer fine powder less than 150um can be eliminated.

[0150] When the catalyst prepared by the method of the present invention is used for ethylene polymerization, the obtained polymer particles have a larger particle size and less polymer fine powder while maintaining a high polymerization activity. The catalyst is suitable for gas phase polymerization process and olefin slurry polymerization process.

[0151] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0152] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0153] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0154] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A catalyst component for olefin polymerization, characterized in that: The catalyst component for olefin polymerization is prepared from raw materials including intermediates, agglomerating agents and reinforcing agents; The intermediate is prepared from raw materials including magnesium halide alcoholate and titanium-containing compound.

2. The catalyst component for olefin polymerization according to claim 1, characterized in that: The magnesium halide alcoholate is a reaction product of a magnesium halide and a low-carbon alcohol; Preferably, The content of low-carbon alcohol in the magnesium halide alcohol compound is 10wt% to 60wt%; or, The molar ratio of the lower alcohol to the magnesium halide is 0.25 to 3, preferably 2 to 3, and more preferably 2 to 2.

8.

3. The catalyst component for olefin polymerization according to claim 2, characterized in that: The magnesium halide alcoholate is selected from at least one of magnesium chloride alcoholates; Preferably, the low-carbon alcohol is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol or isobutanol.

4. The catalyst component for olefin polymerization according to claim 1, characterized in that: The titanium-containing compound is selected from the general formula (I) Ti(OR) m Cl 4-m At least one of the compounds shown; wherein R is C2~C 20 Hydrocarbyl, 0≤m≤4; Preferably, R is C2~C 10 A saturated or unsaturated straight chain, branched chain or cyclic chain hydrocarbon group; More preferably, R is a C2-C6 saturated or unsaturated straight chain, branched chain or cyclic chain hydrocarbon group; Still more preferably, the titanium-containing compound is selected from at least one of titanium tetrachloride, tetraethyl titanate or tetrabutyl titanate.

5. The catalyst component for olefin polymerization according to claim 1, characterized in that: The agglomerating agent is selected from at least one of C1-C8 alkyl ester compounds; Preferably, the agglomerating agent is selected from at least one of C1 to C6 alkyl ester compounds; Further preferably, the agglomerating agent is selected from at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate or isopropyl acetate.

6. The catalyst component for olefin polymerization according to claim 1, characterized in that: The reinforcing agent is selected from at least one of styrene-butadiene block copolymers; Preferably, In the styrene-butadiene block copolymer, the mass content of butadiene is 3 to 97%, preferably 10 to 90%; and / or, The block type in the styrene-butadiene block copolymer is linear or branched; More preferably, The styrene-butadiene block copolymer is selected from at least one of styrene-butadiene diblock copolymer and its derivatives, styrene-butadiene-styrene triblock copolymer and its derivatives; Still more preferably, The styrene-butadiene diblock copolymer derivative is selected from at least one of hydrogenated styrene-butadiene copolymer, maleic anhydride grafted styrene-butadiene copolymer or acrylic acid grafted styrene-butadiene copolymer; The styrene-butadiene-styrene triblock copolymer derivative is at least one selected from hydrogenated styrene-butadiene-styrene copolymer, maleic anhydride grafted styrene-butadiene-styrene copolymer or acrylic acid grafted styrene-butadiene-styrene copolymer.

7. The catalyst component for olefin polymerization according to claim 1, characterized in that: The molar ratio of the titanium-containing compound to the magnesium halide alcoholate is 1 to 100, preferably 5 to 50; and / or, The weight ratio of the intermediate to the agglomerating agent is 0.5 to 50, preferably 1 to 25; and / or, The weight ratio of the intermediate to the reinforcing agent is 10-1000, preferably 20-500.

8. A method for preparing a catalyst component for olefin polymerization, characterized in that: The following steps are involved: (1) reacting a magnesium halide alcoholate with a titanium-containing compound in a solvent, separating the solid from the liquid, and then reacting the separated solid with the titanium-containing compound in a solvent for a second time, washing, and drying to obtain an intermediate; (2) reacting the enhancer, the intermediate and the agglomerating agent in a solvent under a protective atmosphere to obtain the catalyst component; The method is preferably used for preparing the catalyst component for olefin polymerization as claimed in any one of claims 1 to 7.

9. The method for preparing a catalyst component for olefin polymerization according to claim 8, characterized in that: In step (1), the molar ratio of the titanium-containing compound to the magnesium halide alcoholate is 1 to 100, preferably 5 to 50; and / or the molar ratio of the titanium-containing compound for the primary reaction to the titanium-containing compound for the secondary reaction is 0.1 to 10, preferably 0.5 to 5; Preferably, The solvents used in the primary reaction and the secondary reaction are independently selected from C4 to C 20 Alkane or aromatic solvent; preferably, the solvents used in the primary reaction and the secondary reaction are each independently selected from at least one of pentane, hexane, heptane, toluene, isobutane and cyclohexane; and / or, In a single reaction, the concentration of the magnesium halide alcoholate in the reaction system is 1 wt% to 15 wt%, preferably 2 wt% to 10 wt%; and / or, The temperature of the primary reaction and the secondary reaction are independently selected from (-80)°C to 150°C, preferably (-50°C) to 120°C; and / or, The time of the primary reaction and the secondary reaction are each independently selected from 2h to 20h, preferably 4h to 10h; and / or, The drying is carried out by blowing with protective gas.

10. The method for preparing a catalyst component for olefin polymerization according to claim 8, characterized in that: In step (2), The weight ratio of the intermediate to the agglomerating agent is 0.5 to 50, preferably 1 to 25; and / or, The weight ratio of the intermediate to the reinforcing agent is 10 to 1000, preferably 20 to 500; and / or, The concentration of the intermediate in the reaction system is 1 wt% to 15 wt%, preferably 2 wt% to 10 wt%; and / or, The reaction temperature is 0°C to 90°C, preferably 10°C to 50°C; and / or, The reaction time is 0.5h to 6h, preferably 1h to 3h; and / or, Preferably, In step (2), the dispersion of the enhancer is mixed with the dispersion of the intermediate and the agglomerating agent, and then reacted, and then washed and dried to obtain the catalyst component; More preferably, The solvents used in the dispersion of the enhancer and the dispersion of the intermediate are independently selected from C4 to C 20 An alkane solvent or an aromatic solvent; preferably at least one independently selected from pentane, hexane, heptane, toluene, isobutane, and cyclohexane; and / or, The drying is carried out by blowing with protective gas.

11. A catalyst for olefin polymerization, characterized in that: The method comprises: (a) at least one of the catalyst component for olefin polymerization according to any one of claims 1 to 7 and the catalyst component for olefin polymerization prepared by the method according to claims 8 to 10; (b) at least one organoaluminum compound of the general formula AlR'3, wherein the three R's are independently selected from an alkyl group or a halogen-substituted alkyl group.

12. The catalyst for olefin polymerization according to claim 11, characterized in that: The three R's in the organoaluminum compound are independently selected from C1-C8 alkyl groups or C1-C8 alkyl groups substituted with chlorine; preferably, at least one of the three R's in the organoaluminum compound is a C1-C8 alkyl group; Further preferably, the organoaluminum compound is selected from at least one of triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, diethylaluminum monochloride and ethylaluminum dichloride; and / or, In the catalyst for olefin polymerization, the molar ratio of aluminum to titanium is 1-1000, preferably 10-100.

13. Use of a catalyst component for olefin polymerization as claimed in any one of claims 1 to 7, a catalyst component for olefin polymerization prepared by the method according to claims 8 to 10, or a catalyst for olefin polymerization reaction as claimed in any one of claims 11 to 12 in olefin polymerization reaction; preferably, the olefin is selected from one or more of ethylene, propylene, butene, hexene or octene.

Citation Information

Patent Citations

  • Catalyst component preparation method and catalyst for vinyl polymerization

    CN102020732A

  • Preparation method of catalyst component for polymerization of vinyl and catalyst for polymerization of vinyl

    CN102050897A

  • Spherical catalyst for olefinic polymerization

    CN1091748A

  • Catalyst components for the polymerization of olefins

    EP1572756A1

  • Catalyst system for the polymerization of olefins

    EP2285840A1